Measuring Stress : a Guide for Health and Social Scientists. - Cohen, Sheldon (Oxford University Press, 1998)
A resource for health and social scientists who assess the role of stress in their studies of physical and psychiatric illness. The work discusses how stress is conceptualized, how stressors influence onset and progression of psychiatric and physical illness, and how to decide appropriate measures.